2015
DOI: 10.1111/jace.13937
|View full text |Cite
|
Sign up to set email alerts
|

Predictive, Miniature Co‐Extrusion of Multilayered Glass Fiber‐Optic Preforms

Abstract: A miniature co‐extrusion technique, to produce a concentric multilayered glass fiber‐optic preform of ~3 mm diameter, is modeled and experimentally demonstrated. A three‐dimensional, incompressible, noncavitating, and nonisothermal Computational Fluid Dynamics (CFD) model, similar to one developed in our previous work, is used to predict the dimensions of an alternating four‐layer glass stack feed required to produce the desired layer dimensions in a multilayered‐glass preform extrudate, using a miniaturized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Additional physical characterisation of the glasses reveals important information such as composition (EDX), crystallisation (XRD), onset glass transition temperature (Tg) and an assessment of viscosity-temperature behaviour that is used to determine glass preform extrusion and fibre drawing conditions and which once again provides key information simulation activities that support the experimental work [11,12].…”
Section: Chalcogenide Glassesmentioning
confidence: 99%
“…Additional physical characterisation of the glasses reveals important information such as composition (EDX), crystallisation (XRD), onset glass transition temperature (Tg) and an assessment of viscosity-temperature behaviour that is used to determine glass preform extrusion and fibre drawing conditions and which once again provides key information simulation activities that support the experimental work [11,12].…”
Section: Chalcogenide Glassesmentioning
confidence: 99%
“…suggested 3D CFD model of the glass pipe coextrusion process; based on the use of the model, it is possible to determine the stable part of the preform, in terms of constant core/cladding layer geometry. Moreover, Bhowmick et al 13 . used CFD modeling to predict the dimensions of an alternating four‐layer glass stack feed in a miniature coextrusion technique to produce a concentric multilayered glass fiber‐optic preform.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bhowmick et al 12 suggested 3D CFD model of the glass pipe coextrusion process; based on the use of the model, it is possible to determine the stable part of the preform, in terms of constant core/cladding layer geometry. Moreover, Bhowmick et al 13 used CFD modeling to predict the dimensions of an alternating four-layer glass stack feed in a miniature coextrusion technique to produce a concentric multilayered glass fiber-optic preform. Trabelssi et al, 14 using computational simulations, found that at high viscosities of the glass during extrusion of glass preforms, slip occurs at the die/glass interface on the die swell.…”
Section: Introductionmentioning
confidence: 99%
“…In the co-extrusion process, two or more feedstocks are extruded simultaneously. There are two basic possibilities of feedstock arrangement for ceramic co-extrusion: i) the multi-channel or multi-billet extrusion [16,[23][24][25], and ii) co-extrusion of a preform, which is often referred to as feed rod, with serial [20,[26][27][28] or parallel [3,4,19,29,30] ordering of feedstocks in the feed rod. Recently, Kastyl et al [4] have reported on bimaterial core-shell rods composed of dense zirconia toughened alumina (ZTA) core and dense alumina shell that exhibited a combination of high surface hardness of alumina with high fracture force in bending that even exceeded the value of monolithic ZTA.…”
Section: Introductionmentioning
confidence: 99%